2) Determine a raiz de cada
equação:
a) 3 (x + 3) – 1 = 2 resposta x = - 2
b) 3 (x + 2) = 2 (x – 7) resposta x = - 20
c) 3 ( x + 2) – 1 = 2 (x + 3) – 7 resposta x = - 6
d) 3 (x + 1) + 2 = 5 + 2 (x – 1) resposta x = - 2
e) 5 (2X + 7) – 1 = 4 (X – 5) + 9 resposta x = - 15/2

1

Respostas

2014-04-14T19:41:46-03:00
A)3x+9-1=2  ---  x=-6/3    ----x=-2
b)3x+6=2x-14  ----  x=-20
c)3x+6=2x+6-7  ----  x=5-2-2-3  ---- x=-2
d)3x+3+2=5+2x-2  ---  x=5-2-2-3  --- x=-2
e) 10x+35-1=4x-20+9  ---  6x=-20+9-35+1  ---- 6x=-45 --- 2x=-15  ---  x= -15/2